PELUANG DAN TANTANGAN EKONOMI INDUSTRI DI ERA PERDAGANGAN BEBAS - Fatmiati, F; Julianti, Rima; Muharsih, Rani (Jurnal Ekonomi & Bisnis, 2025)
The era of free trade has brought about major changes in the dynamics of international trade, creating various opportunities and challenges for industries seeking access to wider markets. This article analyzes the opportunities and challenges facing industrial economies in the era of global free trade. This article will thoroughly examine free trade, from its basic concepts, benefits and risks, to the latest developments affecting the global economy. Drawing on the theoretical framework of classical free trade, it examines how free trade agreements (FTAs) facilitate market integration, promote economic growth, and attract foreign investment, all of which create significant opportunities for the industrial sector. However, trade liberalization also poses substantial challenges, including intense global competition that can lead to job dislocation, loss of government revenue from tariffs, and regulatory complexity and rules of origin. Furthermore, the article highlights debates surrounding fair trade and equity issues within the global trading system. This article used a qualitative method with a literature review approach. In this context, the literature study method is used as a descriptive basis for compiling an analytical narrative regarding the opportunities and challenges of industrial economics in the free trade era, by utilizing available secondary data comprehensively and systematically. The article concludes by proposing pragmatic adaptation strategies and industrial policies, emphasizing the importance of quality human resources and infrastructure, risk management, and advocacy for fairer trade governance to ensure industrial resilience and growth amidst the dynamics of free trade.